2015
DOI: 10.1155/2015/940243
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Effects of Major Atmospheric Pollutants on Pollen Grains, Pollen Content, and Allergenicity

Abstract: This review summarizes the available data related to the effects of air pollution on pollen grains from different plant species. Several studies carried out either on in situ harvested pollen or on pollen exposed in different places more or less polluted are presented and discussed. The different experimental procedures used to monitor the impact of pollution on pollen grains and on various produced external or internal subparticles are listed. Physicochemical and biological effects of artificial pollution (ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
136
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(148 citation statements)
references
References 255 publications
(271 reference statements)
5
136
0
7
Order By: Relevance
“…It has been shown that PM and diesel exhaust particles can carry allergens from pollen, cat, dog, and house dust mite [130]. Moreover, it has been reported that air pollution increases the allergenic potency of pollen [131][132][133]. In their model based on guinea pigs sensitized to Zinnia pollen, Chelregani et al [134] observed that pollen collected from polluted urban areas not only induced higher levels of serum IgE, but also increased eosinophil counts compared with nonpolluted pollen.…”
Section: Effect Of Air Pollutants On the Airway Epithelium And Respirmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that PM and diesel exhaust particles can carry allergens from pollen, cat, dog, and house dust mite [130]. Moreover, it has been reported that air pollution increases the allergenic potency of pollen [131][132][133]. In their model based on guinea pigs sensitized to Zinnia pollen, Chelregani et al [134] observed that pollen collected from polluted urban areas not only induced higher levels of serum IgE, but also increased eosinophil counts compared with nonpolluted pollen.…”
Section: Effect Of Air Pollutants On the Airway Epithelium And Respirmentioning
confidence: 99%
“…In their model based on guinea pigs sensitized to Zinnia pollen, Chelregani et al [134] observed that pollen collected from polluted urban areas not only induced higher levels of serum IgE, but also increased eosinophil counts compared with nonpolluted pollen. Finally, growing evidence indicates that air pollutants can increase the production of allergens and proinflammatory mediators in pollens as a result of the plant adaptive response to environmental stress [131,135]. In addition, it has been shown that pollens are a source of oxidants [136].…”
Section: Effect Of Air Pollutants On the Airway Epithelium And Respirmentioning
confidence: 99%
“…In addition the term "polluen" has been coined to describe the pollen/pollutant interaction and describe the make-up of pollen materials as they are often carriers of allergenic proteins and non-allergenic pollutants (45). Given the association with pollution and the fact that pollen grains are the major source of outdoor aeroallergens we explore them in particular in this review (46).…”
Section: Aeroallergensmentioning
confidence: 99%
“…Esta situación suscita cada vez más interés, ya que las particularidades del entorno urbano, especialmente la contaminación, hace que los efectos sobre la población sean más notables (Majd et al 2004, Heinrich & Wichmann 2004, Sénéchal et al 2015 incluso cuando las concentraciones polí-nicas sean menores que en entornos rurales (Nicolau et al 2005).…”
Section: Introductionunclassified